Circular Economy Practices and Profitability in Indonesian Manufacturing: Structural Enablers, Barriers, and Sectoral Divergence - Fitria Husnatarina (Nomico, 2025)
The shift toward a circular economy has become increasingly important for Indonesia’s manufacturing industry as firms face rising material costs, environmental pressures, and global competitiveness demands. However, evidence on the profitability implications of circular practices remains fragmented and sector-dependent. This study examines how circular economy implementation influences profitability in Indonesian manufacturing firms through a Systematic Literature Review guided by the PRISMA 2020 protocol. Forty-two relevant studies were synthesized to evaluate the economic effects of practices such as recycling, remanufacturing, industrial symbiosis, eco-design, and service-based business models. The findings indicate that circular adoption enhances profitability mainly through cost efficiency, reduced reliance on virgin materials, operational stability, and new revenue creation. Nevertheless, profitability outcomes diverge across sectors and firm types, shaped by technological readiness, supply chain maturity, access to capital, regulatory certainty, and human capital capability. This review contributes by clarifying the structural conditions under which circular economy practices translate into financial gains in emerging manufacturing contexts.